Tsakhkadzor: The Space оf “Other Spaces” - Saghatelyan, Sona (Journal of Sociology: Bulletin of Yerevan University, 2020)
The relevance and application of Foucault’s concept of "heterotopy" within the framework of the sociological understanding of modern urban space is substantiated. Based on the results of applied sociological research, an attempt was made to consider the space of the resort town and the urban municipal community of Tsaghkadzor as a heterotopy or space of other spaces. This approach allows us to identify the peculiarities of the combination of incongruous elements and, consequently, life contexts in a single space, which violate the seeming continuity and order of the ordinary everyday space.